The BRCA2 mutation status shapes the immune phenotype of prostate cancer - Jenzer, Maximilian; Keß, Peter; Nientiedt, Cathleen; Endris, Volker; Kippenberger, Maximilian; Leichsenring, Jonas; Stögbauer, Fabian; Haimes, Josh; Mishkin, Skyler; Kudlow, Brian; Kaczorowski, Adam; Zschäbitz, Stefanie; et al. (Cancer immunology immunotherapy, 2019)
Defects in DNA damage repair caused by mutations in BRCA1/2, ATM or other genes have been shown to play an important role in the development and progression of prostate cancer. The influence of such mutations on anti-tumor immunity in prostate cancer, however, is largely unknown. To better understand the correlation between BRCA1/2 mutations and the immune phenotype in prostate cancer, we characterized the immune infiltrate of eight BRCA2-mutated tumors in comparison with eight BRCA1/2 wild-type patients by T-cell receptor sequencing and immunohistochemistry for CD45, CD4, CD8, FOXP3, and CD163. In addition, we analyzed seven prostate cancer biopsies that were either BRCA2 or ATM-mutated in comparison with wild-type tumors. Whereas in BRCA1/2 wild-type tumors, immune cells were found predominantly extratumorally, most BRCA2-mutated tumors including one biopsy showed a significantly increased intratumoral immune cell infiltration. The ratio of intratumoral to extratumoral immune cells was considerably higher in BRCA2-mutated tumors for all markers and reached statistical significance for CD4 (p = 0.007), CD8 (p = 0.006), and FOXP3 (p = 0.001). However, the intratumoral CD8 to FOXP3 ratio showed a trend to be lower in BRCA2-mutated tumors suggesting a more suppressed tumor immune microenvironment. Our findings provide a rationale for the future use of immune oncological approaches in BRCA2-mutated prostate cancer and may encourage efforts to target immunosuppressive T-cell populations to prime tumors for immunotherapy.
Gesehen am 04.02.2020